The contribution of a novel PHEX gene mutation to X-linked hypophosphatemic rickets: a case report and an analysis of the gene mutation dosage effect in a rat model - Chen, Xiaoming; Cai, Cijing; Lun, Shaocong; Ye, Qiuli; Pan, Weiyuan; Chen, Yushi; Wu, Yuexuan; Feng, Taoshan; Su, Faming; Ma, Choudi; Luo, Jiaxin; Liu, Meilian; et al. (Frontiers in Endocrinology, 2023)
A Chinese family was identified to have two patients with rickets, an adult female and a male child (proband), both exhibiting signs related to X-linked hypophosphatemic rickets (XLH). Gene sequencing analysis revealed a deletion of adenine at position 1985 (c.1985delA) in the PHEXencoding gene. To investigate the relationship between this mutation and the pathogenicity of XLH, as well as analyze the effects of different dosages of PHEX gene mutations on clinical phenotypes, we developed a rat model carrying the PHEX deletion mutation. The CRISPR/Cas9 gene editing technology was employed to construct the rat model with the PHEX gene mutation (c.1985delA).